G20 and the Erosion of Democracy: Addressing the Decline in Democratic Standards during the COVID-19 Pandemic - Muhammad Habibi; Rizky Dwi Kusuma (Mengeja Indonesia Publisher, 2022)
This study reveals a decline in democratic standards in G20 countries during the COVID-19 pandemic, highlighting the need for dialogue and collaboration to address these challenges. In this research, we employed a descriptive qualitative research design, involving data collection from various sources and analyzing trends in the Democracy Index scores of G20 countries between 2020 and 2021. Additionally, we conducted case studies and expert interviews to understand the pandemic's impact on democratic standards in G20 countries. The G20 Summit offers an opportunity to support democratic principles when addressing global issues, such as sustainable energy transition, digital transformation, and global health governance. Civil society organizations and C20 meetings play a crucial role in enhancing democracy in G20 countries by promoting transparency, accountability, and citizen participation. The research findings emphasize the importance of addressing the decline in democratic standards among G20 countries, with the G20 Summit in Bali serving as a platform to strengthen democratic values and develop more inclusive and effective policy responses.